Comparison of circulating total sFLT-1 to placental-specific sFLT-1 e15a in women with suspected preeclampsia. (24th March 2022) - Rowson, S.; Reddy, M.; De Guingand, D.L.; Langston-Cox, A.; Marshall, S.A.; da Silva Costa, F.; Palmer, K.R.
Abstract: Introduction: Soluble fms-like tyrosine kinase 1 (sFLT-1), a circulating anti-angiogenic factor that binds and antagonizes placental growth factor (PlGF), appears key to preeclamptic pathophysiology. Two main sFLT-1 splice variants exist: sFLT-1 e15a and sFLT-1 i13. Total sFLT-1/PlGF ratios are increasingly used clinically; we explore whether using placental-specific sFLT-1 e15a improves test performance compared with total sFLT-1 in preeclampsia diagnosis. Methods: Consent was obtained for serum sampling from 96 women with suspected preeclampsia. Total sFLT-1 and PlGF were quantified using the B.R.A.H.M.S Kryptor Compact Plus automated immunoassay platform, and sFLT-1 e15a by custom enzyme-linked immunosorbent assay. Test performance was then assessed by subsequent diagnosis. Results: Of 96 participants, 32 did not develop preeclampsia, 32 had early-onset (<34 weeks') disease and 32 had late-onset (≥34 weeks') disease. In those with preeclampsia, median sFLT-1 and sFLT-1 e15a were significantly increased (7361.0 vs 2463.0 pg/mL, and 946.6 vs 305.4 ng/mL respectively; p < 0.001 for both), and PlGF significantly reduced (43.5 vs 154.4 pg/mL; p < 0.001) compared to those without preeclampsia. Those with early-onset, compared to late-onset, preeclampsia chiefly had lower median PlGF levels (16.0 vs 57.3; p < 0.001), which contributed to higher sFLT-1/PlGF and sFLT-1 e15a/PlGF ratios (830.1 vs 86.7, and 109258.9 vs 12608.7 respectively; p < 0.001 for both). Discussion: sFLT-1 e15a performs comparably to total sFLT-1 in women with suspected preeclampsia, however with higher translational burden. Our results support the expanding clinical use of the sFLT-1/PlGF ratio in suspected preeclampsia, particularly early-onset, to assist with disease diagnosis.